2018
DOI: 10.2478/ijm-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the layers of a market-oriented organisational culture

Abstract: Organisations with market-oriented cultures outperform other organisations. Thus, the creation of such a culture is paramount. This paper details how distinct layers of an organisation’s culture can in combination influence market-oriented behaviours. The importance of organisational culture in the successful implementation of a market orientation strategy has been recognised. However, an awareness of how the layers of organisational culture, such as values, norms and artefacts, can contribute to market-orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…However, a deeper understanding of artefacts is required (Homburg and Pflesser, 2000; Farrell, 2005; Byrne et al , 2019; Tiernan et al , 2019). The focus on and detail of artefacts as an entity within a market-oriented culture is limited and includes inconsistencies (Farrell, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a deeper understanding of artefacts is required (Homburg and Pflesser, 2000; Farrell, 2005; Byrne et al , 2019; Tiernan et al , 2019). The focus on and detail of artefacts as an entity within a market-oriented culture is limited and includes inconsistencies (Farrell, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Norms can be defined as expectations about behaviour that are shared by a social group and relate directly to market-oriented values (Homburg and Pflesser, 2000; Gebhardt et al , 2006; Byrne et al , 2019). Artefacts are recognised in the literature as being a crucial element of culture (Taras et al , 2009) possessing strong symbolic meaning (Hatch, 1993; Homburg and Pflesser, 2000; Farrell, 2005; Schein, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceptions and values of employees regarding what constitutes a marketing orientation have been found to correspond to performance of employees in HEIs (Webster -Hammond 2018). However, the expectation of a single uniform perception of what is meant by market orientation in this context seems unlikely (Akonkwa 2009;Byrne et al 2019), especially given the potential emergence of subcultures in large complex organisations such as HEIs (Gregory 1983). Despite this, heterogenous subcultures have the potential to deepen and develop our understanding of the concept of market orientation in the HE context (Tummons 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Hence ISME firms have to consistently 'act market-oriented to keep up competitive advantage' as suggested by Kumar et al (2011). In their study, Byrne, Dwyer and Doyle (2018) looked at organizational cultural layers in the implementation of MO amongst Irish firms. They concluded that 'organizational cultural values (r=0.74), norms (r=0.75 and artifacts were found to influence marketoriented behaviours' (p.26).Appiah-Adu (1998) and Osuagwu and Obaji (2009) identified some linkages in the relationship between MO and performance in the manufacturing sector of the developing economies of Ghana and Nigeria respectively.…”
mentioning
confidence: 99%